Peran Pendidikan Keluarga dalam Pencegahan Bahaya Narkoba pada Remaja - Ati Kusmawati; Aprilia Cahyani; Layla Fitri; Zalfa Sofia Avrianti Arifin (WISSEN : Jurnal Ilmu Sosial dan Humaniora, 2025)
Drug abuse among adolescents is a serious problem that requires comprehensive and sustainable prevention efforts. Adolescence is a developmental phase characterized by the search for identity, emotional instability, and high levels of influence from the social environment, including peers. In this context, family education plays a central role as the first line of defense in protecting adolescents from the negative influence of drugs. Through open communication, wise supervision, and consistent love and emotional support, parents can create a safe and supportive environment for their children's mental development. Effective family education includes strengthening moral, religious, and social values, aiming to shape adolescents' character and resilience to environmental pressures. In certain situations, family education also needs to be supported by a scientific approach, one of which is Cognitive Behavioral Therapy (CBT). CBT is a psychological approach that focuses on improving negative thought patterns and behaviors. In the context of discussing drugs, CBT can help adolescents identify the emotional and social triggers that lead them to try illicit substances and equip them with strategies to cope healthily. The integration of family education and CBT therapy creates a comprehensive approach—from the home to professional support—to strengthen adolescents' mental resilience. This collaboration not only reduces the risk of addiction but also encourages adolescents to become more self-aware, emotionally healthy, and productive individuals. Therefore, synergy between families, schools, and mental health professionals is crucial in creating a drug-free generation of young people ready to face the challenges of modern life. Therefore, the active involvement of all parties, including educational institutions and the community, is essential to creating an environment that supports early drug prevention.